JUDI DOMINO DIKALANGAN REMAJA DI DESA TANJUNG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Rezki Rinaldi; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The title of this research"Domino Gambling among Adolescents in Tanjung Village, Koto Kampar Hulu Subdistrict, Kampar Regency." The aims of this research to explain how the gambling behavior among adolescents in Tanjung Village and how social supervision is carried out by the community from adolescent gambling behavior. The author used George Homans' Social Exchange Theory and Social Control Theory to analyze the phenomenon of this research. The method of this research is descriptive qualitative research. this research is presented and analyzed in the form of descriptive (descriptive) words with a qualitative approach.  In addition, this research is also supported by conducting in-depth interviews with informants (informants) that have been determined by researcher in advance.  The author interviewed 8 informants consist of three teenage boys who took part in gambling, three teenage parents of gamblers, one school teacher, and one local RW and officer. Based on the results of the interviews, we obtain information that is very supportive for the validity of the data that is focus of the research.  Based on the results of the research, teenagers in Tanjung Village use the Domino game as a means to play gambling, where the game uses money as a bet given to the winners in the game of domino gambling.  The player who gets the most of money, at the same time is a sign that he is the winner in gambling and this is where the core of the domino gambling game lies.  From the adolescent domino gambling behavior, it is known that there is still a lack of social control carried out by the community, especially from parents, school teachers, and also the environment in which gambling activities are carried out by teenagers in Tanjung Village. Keywords: Teenagers, Gambling Behavior, Domino Gambling, Community Oversight.